Specific labeling of the Bacillus subtilis chromosome terminus. - Sargent, M G (1980)
The deoxyribonucleic acid labeled by a procedure described previously for labeling the chromosomal terminus of B. subtilis 168 was substantially enriched for sequences homologous to bacteriophages SP beta and phi 3T, which integrate in the terminal region.